Indonesian Science Teachers' Ability to Design Scientific Literacy Test - Qadar, Riskan; Haryanto, Zeni; Subagiyo, Lambang; Junus, Muhammad; Syam, Muliati (International Journal of STEM Education for Sustainability, 2022)
The ability of junior high school teachers to design scientific literacy tests is necessary. This research is focused on finding out how teachers can elaborate their ability to design scientific literacy tests. There are eight indicators related to scientific literacy in the developed instrument. We analyzed 41 packages in junior high schools from 9 regencies/cities in Indonesia. Based on the analysis, it was found that there were indicators that had not been achieved because curriculum materials were not available in that semester. This study shows that Indonesian science teachers can develop tests containing scientific literacy with an average of 76.4% of all scientific literacy indicators.